(untitled) (Czech Journal of International Relations, 2000)
The demise of the USSR and its Marxist ideology, the emergence of Russia once again as an independent, autonomous entity and the changes following the end of the Cold War compelled Russia to redefine its national interests and make substantial adjustments in the sphere of foreign policy and in the conceptual foundation of international strategy. The essay deals with the development of the discipline of international relations in Russia during the 1990s. Its author seeks to draw a distinction between and describe the major theoretical approaches and foreign political schools in the country, to outline the problem of the Russian debate about international relations and reflect the institutional dimension of post-communist international studies. In post-communist Russia, there were and still are several schools of foreign political thinking, differing in their conceptual foundations and in their approach to specific international problems. Together with purely Russian schools, one can identify here almost all classic paradigms of international relations (realism, idealism or globalism/radicalism/structuralism). But one must realize that the mentioned schools represent changeable arrangements. In the initial phase, following the establishment of independent Russia, its international policy was most strongly influenced by Atlanticism which was orientated to the West. This was followed by the assertion of Euro-Asianism which placed greater stress on the uniqueness of a Russia which ought to become a bridge between West and East. The “derzavnici”, on the other hand, were of the opinion that Russia should be guided by the principle of self-restriction and self-sufficiency, but this notwithstanding, it should pursue an active foreign policy with the aim of demonstrating to the West the capability of Russia as a counter-balance to the enlargement of NATO and the European Union. The realists helped to overcome the crisis in Russian foreign political thinking; they succeeded in defining the real security interests and priorities of Russia (for example, preserving the common system of European security or preventing the enlargement of NATO into its vicinity). The geopolitical school, in turn, exhorted the restoration of the country’s former great power status since it maintained that the present system of international relations was multi-polar. The idealists, on the other hand, concentrated primarily on the problem of the integration of the CIS and on European security.